Integrin-targeted pH-responsive micelles for enhanced efficiency of anticancer treatment in vitro and in vivo. Issue 10 (14th March 2015) - Liu, Jinjian; Deng, Hongzhang; Liu, Qiang; Chu, Liping; Zhang, Yumin; Yang, Cuihong; Zhao, Xuefei; Huang, Pingsheng; Deng, Liandong; Dong, Anjie; Liu, Jianfeng
<x xml:space="preserve">Abstract</x> Integrin-targeted pH-responsive micelles were synthesized with an enhanced drug-loading efficiency, tumor-targeting ability and pH-controlled intracellular drug release for enhanced tumor treatment.